Exhaustible Resources, Technology Choice and Industrialization of Developing Countries - Erika Färnstrand Damsgaard (Research Institute of Industrial Economics (IFN), 2010)
How should the world economy adapt to the increased demand for exhaustible resources from countries like China and India? To address that issue, this paper presents a dynamic model of the world economy with two technologies for production; a resource technology which uses an exhaustible resource as an input and an alternative technology, which does not. I find that both the time path of resource extraction and the adoption of the alternative technology depend on the optimal allocation of capital across the technologies, and the size of the capital stock in relation to the resource stock. In particular, if the capital stock is small, only the resource technology is used initally, and the alternative technology is adopted with a delay. Next, the model is calibrated to analyze the eects of industrialization of developing countries on the extraction of oil and technology choice for energy production. As a result of industrialization, resource extraction increases and the alternative technology is adopted earlier.
Keywords: Q30; Q40; 330; Exhaustible resources; Technological change; Erschöpfbare Ressourcen; Technischer Fortschritt; Internationale Wirtschaft; Industrialisierung; Erdölgewinnung; Theorie